Burnout and moral injuries after foreign deployment among medical personnel of the German armed forces: a pre-post study - Langner, Franziska; Börke, Anna Katharina; Muschner, Patric; Muther, Maria; Reichelt, Andreas; Willmund, Gerd-Dieter; Wesemann, Ulrich; Zimmermann, Peter Lutz; Schönsee, Isabel (Frontiers in Psychiatry, 2024)
Introduction: Workplace stressors make burnout syndrome highly relevant for medical service soldiers. This study examines the effects of moral injuries and personal values after foreign deployment. Materials and Methods: In this longitudinal study 91 German Medical Service soldiers completed the Maslach Burnout Inventory (MBI) and Portrait-Value-Questionnaire (PVQ) pre- and post-deployment and Moral Injury Scale (SMBE) post-deployment. T-tests assessed changes in MBI and PVQ scores pre- and post-deployment. Correlations between moral injuries (MI), MBI and PVQ scores were examined. Results: MBI subscales indicated mild to moderate burnout symptoms pre- and post-deployment, with slight but non-significant deterioration. No significant differences in PVQ scores were found. PVQ self-direction and tradition at t1 correlated negatively with MBI INV at t2 (PVQ SD r = -.21, p = .043) and MBI PA at t2 (PVQ TR r = -.23, p = .027). PVQ power at t1 correlated positively with MBI PA at t2 (PVQ PO r = .28, p = .006). MI at t2 correlated with MBI subscales Emotional Exhaustion (EE; r = -.54, p = .001), Depersonalization (DP; r = .38, p = .001), and Involvement (INV; r = .30, p = .004) before and after deployment. Conclusion: Medical service soldiers exhibit mild to moderate burnout symptoms before deployment. Significant associations between MI and burnout were found in three MBI subscales. Personal values may predict burnout, suggesting the need for detailed studies on work stress among soldiers to inform prevention approaches.